Raymond Hopes. (28th July 2018) - Rossdale, Peter; Hunt, Michael; Peace, Colin; Ricketts, Sidney; Digby, Nicholas Wingfield; Greet, Timothy; Steven, Neil; Pilsworth, Robert; McGladdery, Andrew; Carson, Deidre; Barrelet, Frederic; Shepherd, Michael; et al.
Abstract : One of Rossdales early partners, he developed the racehorses‐in‐training services of the Newmarket practice, stimulating the development of new diagnostic and therapeutic techniques that are taken for granted today.